The Role of Gending Bapang Malang as a Relaxation-Based Intervention for Adolescents with Anxiety: An Analytical Study: Kajian Analisis Instrumen Gending Bapang Malang Sebagai Media Intervensi Relaksasi Bagi Remaja yang Mengalami Anxiety - Agusti Mardikaningsih; Praharisti Kurniasari (Proram studi pendidikan Sejarah Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2025)
This study examines the potential of Gending Bapang Malang, a traditional Javanese gamelan piece, as a relaxation intervention for adolescents experiencing anxiety. Using a quasi-experimental pre-test post-test control group design, sixty adolescents aged 15–18 years were recruited and divided into two groups: an experimental group (n=30) exposed to Gending Bapang Malang and a control group (n=30) exposed to modern instrumental music of similar tempo. Anxiety levels were measured using the Depression Anxiety Stress Scales (DASS-21), while physiological responses were assessed via Heart Rate Variability (HRV). Semi-structured interviews were also conducted to capture subjective experiences. Results indicated a significant reduction in anxiety scores in the experimental group (Δ = -6.7, p < 0.01), compared to a non-significant reduction in the control group (Δ = -1.9, p = 0.072). HRV increased substantially in the experimental group (+16.6 ms, p < 0.01), while the control group showed minimal improvement. Musicological analysis revealed that Gending Bapang features a slow tempo (68 bpm), repetitive gong cycles, and low-frequency resonance, which contribute to relaxation effects. Qualitative findings highlighted feelings of calmness, improved sleep, enhanced focus, and cultural pride among participants. These results suggest that Gending Bapang Malang is an effective, culturally grounded intervention for reducing adolescent anxiety, offering both psychological and physiological benefits. Its integration into school counseling and community-based mental health programs holds promise for culturally responsive mental health care in Indonesia.